Death of Bahrun Naim : Mastermind of Terror in Southeast Asia - Gunaratna, Rohan (2018)
The death of Bahrun Naim, the directing figure of terrorist attacks in Southeast Asia, demonstrates that by working together, governments can prevent and pre-empt attacks.